Answer: B
Step-by-step explanation:
Solve the equation by substitution method.
To get b-2-3b=4. Then you substitute b into simplest to get, b=-3. Repeat the same process with a to get, a=-5. So your answer would be (-5, -3)
Step-by-step explanation:
Given that,
Two equations,
3x + 11 = 11 .....(1)
And
3(x - 3) = 45
or
3x-9=45 ....(2)
Subtract 11 on both sides of equation (1).
3x + 11-11 = 11-11
3x=0
x = 0
Add 9 to both sides of equation (2)
3x-9+9=45+9
3x = 54
x = 18
Hence, the solution of equation (1) is x=0 and form equation (2) x = 18.
Answer:
volved with elements and compounds composed of atoms, molecules and ions: their composition, structure, properties, behavior and the changes they undergo during a reaction with other substances.